Antioxidants markers of professional soccer players during the season and their relationship with competitive performance - Ponce-Gonzalez, J. G.; Corral-Pérez, J.; de Villarreal, E. S.; Gutierrez-Manzanedo, J. V.; De Castro-Maqueda, G.; Casals, C. (Journal of Human Kinetics, 2021)
The aim of this study was to assess antioxidant markers before and after a mid-season of professional soccer players from the 3rd Spanish Division, and to correlate antioxidant markers with competitive performance. Sixty-five male players (age = 25.3 ± 4.2 yr, body mass = 73.2 ± 6.7 kg, body height = 177.8 ± 5.7 cm) from three soccer clubs from Cádiz (Spain) participated in the study. Body composition, maximal aerobic capacity (VO2max), and baseline antioxidant blood markers (Total Antioxidant Status (TAS) and Reduced glutathione/Oxidized glutathione ratio) were assessed in the first week of the championship season (pre-test) and after 18 weeks in the mid-season (post-test). Soccer performance was registered according to the official classification ranking at both the mid-season and at the end of the season; ranking positions for Team A were 2nd and 1st, for Team B were 5th and 5th, while for Team C were 12th and 14th, respectively. Regression analyses showed that TAS and VO2max were able to independently predict (p < 0.05) performance in our participants. Moreover, antioxidant levels showed significant main effects on performance (p < 0.001); where a higher antioxidant capacity was observed in the best performance soccer team, both before and after the mid-season. Notwithstanding, the competitive period compromised the antioxidant status since TAS levels significantly decreased after the 18-week training program and competition compared with baseline values in all soccer teams (p < 0.001). These results suggest the need of monitoring antioxidants in soccer players to prevent excessive oxidative stress and cellular damage which could compromise success in competition, by adjusting the training loads, diet or ergogenic aids, if needed.